Regulating Effects of Climate, and Net Primary Productivity Depends on Soil Organic Carbon Sequestration - Mr. Ashok Kumar Das, Prof. Dinabandhu Jena, Prof. Manoranjan Pattnaik (International Journal of Modern Agriculture, 2020)
According to the Kyoto Protocol, sequestration of carbon in terrestrial habitats is a low cost alternative for reducing the rising concentrations of CO2 in the atmosphere. It was known that the trees of the planet and their soils have a high capacity for sequestration of the atmospheric carbon. Scientists have been growing interest in terrestrial soil carbon storage processes for the last two decades. This study sought to summarize the significant chronological progress of research on sequestration of soil organic carbon (SOC) and also to underpin the issues that have yet to be based on this research at global level. Work on SOC sequestration started in the early seventies where most studies estimated the size / stock of the global SOC. Many of the researchers started to concentrate in the early 1980s on the factors involved in preserving organic carbon in various habitats. Subsequently, the researchers started to focus on various types of SOC pools in different types of habitats, their scale, turnover and chemical characterization. The researcher recently reported on the temperature sensitivity of organic carbon in different forms of soil and its stabilization mechanism. Researchers have been interested in the contribution of microbial derived carbon in recalcitrant SOC pool and in their sequestration cycle in different types of ecosystems. The investment in SOC sequestration work into the fate of sequestered carbon in various soil types and their stabilization mechanisms is undoubtedly inadequate. India is the nation that stretches through regions from temperate to dry desert zones with different forms of vulnerable habitats and susceptibility to global climate change.